2018
DOI: 10.15761/crr.1000145
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of p16INK4a in human cancers – a new biomarker?

Abstract: The ARF and INK4a genes are located in the same CDKN2a locus, both showing its tumor suppressive activity. ARF has been shown to detect potentially harmful oncogenic signals, making incipient cancer cells undergo senescence or apoptosis. INK4a, on the other hand, responds to signals from aging in a variety of tissues including islets of Langerhans, neuronal cells, and cancer stem cells in general. It also detects oncogenic signals from incipient cancer cells to induce them senescent to prevent neoplastic trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 91 publications
1
37
0
Order By: Relevance
“…The p16 INK4a cyclin-dependent kinase inhibitor (CDKN2a) has been implicated in replicative senescence, the state of permanent growth arrest driven by cell divisions or constitutive Ras-Raf-MEK signaling (see 131134 for p16 INK4a reviews; Fig. 2).…”
Section: Ets1 and Ets2mentioning
confidence: 99%
See 1 more Smart Citation
“…The p16 INK4a cyclin-dependent kinase inhibitor (CDKN2a) has been implicated in replicative senescence, the state of permanent growth arrest driven by cell divisions or constitutive Ras-Raf-MEK signaling (see 131134 for p16 INK4a reviews; Fig. 2).…”
Section: Ets1 and Ets2mentioning
confidence: 99%
“…The p16 INK4a cyclin-dependent kinase inhibitor is implicated in replicative senescence, the state of permanent growth arrest caused by cumulative cell divisions or constitutive Ras-Raf-MEK signaling (50). p16 INK4a is an essential tumor suppressor that prevents the emergence of incipient cancer cells (134). The gene expression is regulated at the transcription level and thus the promoter analysis is critical (135, 136).…”
Section: Ets1 and Ets2mentioning
confidence: 99%
“…For all these genes, except ZMAT3, high expression was associated with inferior OS (Fig 1B, C and Figure S1). Functional annotation of these genes revealed that MDM2 is a direct negative regulator of TP53; CDKN2A encodes for p16 and p14arf, both tumour suppressor proteins regulating cell cycle (Inoue & Fry, 2018); GTSE1 is a protein regulating apoptotic signalling and cell migration and is associated with chemotherapy resistance (Guo et al, 2016); ZMAT3 encodes a protein containing three zinc finger domains and has been shown to inhibit tumour cell growth when overexpressed (Guo et al, 2011); RRM2B, or p53R2, encodes an enzyme named ribonucleotide reductase regulatory TP53 inducible subunit M2B, responsible for generating nucleotide precursors required for DNA replication and is essential for normal DNA repair (Yamaguchi et al, 2001). Although correction of p-values for multiple testing resulted in loss of statistical significance of all genes except GTSE1, we evaluated all five genes for clinical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Because of this pathway, p16 dysregulation has been correlated to many malignancies, including cervical cancer. Eventually, E7 mediates the modification of host histone architecture; among these, p16 promoter will also be activated, causing an even higher expression of the protein [119][120][121]. On the other hand, patients with cervical cancer have less expression of p16 due to hypermethylation of its promoter, leading to unsuccessful suppression of tumor growth, and therefore allowing cancer When a cell has to go through G1/S transition, the cyclin-dependent kinases 4 and 6 (CDK4/6) forms a complex with cyclin D. The entire complex phosphorylates the retinoblastoma protein (pRb), which, in normal conditions, binds the transcription factor E2F.…”
Section: P16 Ink4amentioning
confidence: 99%